2015
DOI: 10.1039/c4ra12156b
|View full text |Cite
|
Sign up to set email alerts
|

Effective formulation and processing of nanofilled carbon fiber reinforced composites

Abstract: This work describes a successful approach toward the development of a carbon fiber-reinforced composite based on an optimized nanofilled resin for industrial applications. The epoxy matrix is prepared by mixing a tetrafunctional epoxy precursor with a reactive diluent which allows reduction of the viscosity of the epoxy precursor and facilitation of the dispersion of 0.5% wt multiwall carbon nanotubes. The proper choice of the viscosity value and the infusion technique allow improvement of the electrical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 25 publications
0
57
0
Order By: Relevance
“…The selected MWCNTs concentration was of 0.5 wt%. The selected concentration of the MWCNTs has been proved to offer sufficient electrical conductivity to composite aerostructures resulting to an effective dissipation of lightning currents during flight , while the mixture is characterized by good dynamic mechanical behavior . An ultra‐sonication for 20 min has been used in order to achieve a uniform dispersion of 0.5 wt% MWCNTs within the epoxy matrix.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected MWCNTs concentration was of 0.5 wt%. The selected concentration of the MWCNTs has been proved to offer sufficient electrical conductivity to composite aerostructures resulting to an effective dissipation of lightning currents during flight , while the mixture is characterized by good dynamic mechanical behavior . An ultra‐sonication for 20 min has been used in order to achieve a uniform dispersion of 0.5 wt% MWCNTs within the epoxy matrix.…”
Section: Methodsmentioning
confidence: 99%
“…As far as the electrical conductivity is concerned, the obtained values for the electrical conductivity of the filled with both MWCNTs and GPOSS resin is 3.5 × 10 −3 S/m; it is appreciably higher as compared to 8 × 10 −13 S/m of the unfilled material. It was found that the electrical percolation threshold (EPT), i.e., the transition from the insulating to conducting electrical behavior is exceeded for a MWCNTs concentration value in the ranges between 0.1 and 0.32 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…This particular epoxy formulation has proven to be very effective for improving nanofiller dispersion due to a decrease in the viscosity [19e22] and, in addition, it has been found to reduce the moisture content which is a very critical characteristic for aeronautic materials [19,23]. Furthermore, in order to minimize the filtration effects [24,25], the traditional liquid infusion process has been modified as described in the sequel.…”
Section: Introductionmentioning
confidence: 99%
“…From an electrical perspective, the carbon fibre has a high electrical conductivity of 40-50 kS/m, but the resin is considered to be an electrical insulator [19]. The wavy nature of carbon fibres, due to imperfections occurring during the manufacturing process or degradation of the material, may cause fibres to touch both between plies and within the same ply.…”
Section: Overview Of Cfrp Materialsmentioning
confidence: 99%